Think Pink – Installation et interprétation poétique situationnelle : poser un regard autre sur le quotidien par l’intervention artistique - Jérémie Bellemare (Conserveries Mémorielles)
My work is contextual research, carried out in pursuit of the observation of the hic and nunc (here and now) situational. How to disrupt everyday life through non-places by artistic interventions? My research is based on the study of specific space in real time, taking a look at the human, architectural and urbanistic components that characterize them, so that they can intervene artistically. This project was realized by the integration of an ephemeral work in a place that is not dedicated to art; the bridge Sainte-Anne in the city of Chicoutimi. I will address the issue of the relation that individuals have to the space attached to the place invested by Think Pink. The situational phenomenon which alters the temporality seen daily by the users of this non-place will also be questioned. I will discuss the technical aspects, from design to realization, as well as the various methods used at the heart of the creative process of this artistic project carried out in the summer of 2015.